TRANSLATION AND VALIDATION OF NARROW PERSONALITY TRAITS FROM IPIP AMONG MALAYSIAN CIVIL SERVANTS - Muhammad Faeez Zakaria; Harris Shah Abd Hamid; Nurul Shahnaz Ahmad Mahdzan, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Numerous psychological instruments can be used to assess personality, including those from the IPIP website. Portions from the IPIP measures had been translated and validated in Malaysia with unclear validity evidence. Additionally, narrow traits (from the broad five factors) had not been examined in the Malaysian civil servant’s context. As part of a research project examining over-indebtedness among civil servants, this study attempted to validate 11 narrow traits (89 items). Back translation into Bahasa Melayu involved adapting the items to be culturally appropriate. Through expert validation, pre-testing, and a survey of Malaysian civil servants, it was determined that the narrow traits demonstrated good internal consistency, albeit with some items removed. Exploratory Factor Analysis based on data from 134 civil servants and Composite Reliability as well as Discriminant Validity (SmartPLS Analysis) based on data from 490 civil servants provided evidence that the 11 narrow traits have satisfactory structural validity. However, the traits tend to be structurally separated based on wording direction (positive vs negative). It can be concluded that the Bahasa Melayu version is appropriate for measuring the personality of Malaysian civil servants.